2019
DOI: 10.3906/sag-1812-49
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of PTEN by hexarelin attenuates coronary artery ligation-induced heart failure in rats

Abstract: Background/aim: Hexarelin is a synthetic growth hormone-releasing peptide that exerts cardioprotective effects. However, its cardioprotective effect against heart failure (HF) is yet to be explained. This study investigated the therapeutic role of hexarelin and the mechanisms underlying its cardioprotective effects against coronary artery ligation (CAL)-induced HF in rats.Materials and methods: Rats with four weeks of permanent CAL, induced myocardial infarction, and HF were randomly separated into four groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Despite variability of the independent replicates, likely because of challenges with tissue isolation (Experimental Procedures), we identified similarities in gene expression, including overexpression of the genes encoding BMP1 , growth hormone secretagogue receptor ( GHSR ) and a putative serine proteinase inhibitor ( PI ). These genes had robust expression following injury, and were previously shown to have roles in tissue repair and wound healing in other organisms 18‐21 . In addition, these genes were differentially expressed in the distal vs. the proximal siphon pieces (Figure 2), showing increased expression of BMP1 , GHSR , and PI at 24 hpa in the necrotic distal fragments and low expression levels in the proximal fragments at this time point, comparable to that of controls.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…Despite variability of the independent replicates, likely because of challenges with tissue isolation (Experimental Procedures), we identified similarities in gene expression, including overexpression of the genes encoding BMP1 , growth hormone secretagogue receptor ( GHSR ) and a putative serine proteinase inhibitor ( PI ). These genes had robust expression following injury, and were previously shown to have roles in tissue repair and wound healing in other organisms 18‐21 . In addition, these genes were differentially expressed in the distal vs. the proximal siphon pieces (Figure 2), showing increased expression of BMP1 , GHSR , and PI at 24 hpa in the necrotic distal fragments and low expression levels in the proximal fragments at this time point, comparable to that of controls.…”
Section: Resultsmentioning
confidence: 67%
“…These genes had robust expression following injury, and were previously shown to have roles in tissue repair and wound healing in other organisms. [18][19][20][21] In addition, these genes were differentially expressed in the distal vs. the proximal siphon pieces (Figure 2), showing increased expression of BMP1, GHSR, and PI at 24 hpa in the necrotic distal fragments and low expression levels in the proximal fragments at this time point, comparable to that of controls. These results indicated that there were similarities in injury-induced gene expression at different injury sites.…”
Section: Assay For Studying Injury Response In P Mytiligeramentioning
confidence: 93%
“…In vivo infarct therapy effect was evaluated by measuring the infarct size, which is considered to be a critical indicator to evaluate the cardiac damage (Ramachandra et al, 2020 ). Coronary artery ligation is a widely used method to establish the AMI rat model for the evaluation of the in vivo infarct therapy effect, because it is more clinically relevant to imitate the clinical status of patients (Agbo et al, 2019 ). MTP/RGD-CAL/TAN NS exhibited better infarct size reduction effect compared with MTP-CAL/TAN NS and CAL/TAN NS, suggesting the modification effect of the double modification of MTP-131 and RGD peptide.…”
Section: Discussionmentioning
confidence: 99%
“…The exertion of those reported cardioprotective effects by hexarelin is achieved by binding to either cardiac non-growth hormone secretagogue receptor CD36 or the growth hormone secretagogue receptor-1a (2). Some of the beneficial cardiovascular functions of hexarelin include its antiatherosclerotic functions (3), suppression of cardiac fibrosis (4,5), anti-apoptotic effects (6,7), and cardiac output improvement (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%